Prufrock: The Delegate of Modern Man (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The ‘Love Song of J. Alfred Prufrock,’ a great work of art by the great modern poet and critic T. S. Eliot, started in 1911 was published in 1917 after the publication of the “Preludes” (1915). It is considered, a dramatic monologue as Tennyson’s ‘Ulysess’ and has been composed in the pattern of Stream of Consciousness. It is the poetry of anguish against the growing materialism augmented by the impact of the World-War I (1914-1919). The trauma of the war lingered, making people apprehensive of the uncertainty of the situation and difference of the gigantic problems of life. Materialism and commercialism appeared to choke the human emotion and feelings that led the poets to attack the trend with wit and irony. The Epigraph taken from Dante’s ‘Inferno’ forms the root image of the poem.  The Epigraph suggests the vagueness of the speaker’s thought but the images are quite distinct and the range of wit is very wide. The opening line of the poem with their colloquial language presents a break from Victorian poetry –‘Let us go then You and I.’ [1]Prufrock has nursed love in his heart but has not been able to convey his feelings to his beloved. He ponders:‘we have lingered in the chambers of the sea.’ [2]Time has moved to form a bald on the middle portion of his head, yet he has not been able and courageous enough to cough out his feelings to his beloved and nor he feels the need of a face to meet the ‘faces we meet.’He is in the ‘Autumn’ of life advancing to ‘Winter’, yet is unable to express his love to his beloved, although he has been craving for the same since long and has been procrastinating and idle only fancying: ‘There will be time there will be time.’ [3] suggesting his belief that there is a reason for every happening, taking place everywhere.He evaluates himself that he has lived a club life having no life force save the passing of days and has measured his life with ‘coffee-spoons.’Prufrock suffers from inaction and indecision that reminds us of Hamlet, the prince of Denmark who had divided-self oscillating between ‘to be or not to be.’